APPLICATION OF LAVENDER AND MINT ESSENTIAL OILS FOR IM-PROVEMENT OF ALFALFA (MEDICAGO SATIVA L.) SEED QUALITY - Tabakovic, Marijenka; Dragičević, Vesna; Brankov, Milan; Stanisavljević, Rade; Poštić, Dobrivoj; Perić, Vesna; Oro, Violeta (Journal on Processing and Energy in Agriculture, 2023)
Essential oils (Eos) are widely utilised in agriculture. The study's objective was to examine the impact of Eo'son alfalfa (Medicago sativa L.) seed dormancy.The four different varieties of alfalfa were used for the experiment (Zaječarka, Banatska, K-28, Novosadska). Two essential oils, lavender (LavandulaangustifoliaMill.) and mint (Menthapiperita L.) were applied to seeds at four concentrations:1%, 0.5%, 0.2%, and 0.02%, along with water as a control. Germination, dormant seeds and dead seeds were evaluated in a laboratory setting according to ISTA rules.The type of Eos had no discernible influence on germinated seeds, dormancy, and dead seeds. Both oils in concentrations of 1% and 0.5% inhibited seed germination. The maximum germination of 91.66% was achieved with the Novosadska variety using lavender oil at a concentration of 0.02%, with reduced dormancy. Varieties Zaječarka and Banatska had the highest level of dead and dormant seeds when lavender and mint Eos were applied at a concentration of 0.2%. This study showed that both Eos at a concentration of 0.02% had a stimulatory effect on seed germination, simultaneously reducing seed dormancy, emphasizing their potential use for seed quality improvement in organic farming.
Keywords: essential oils, concentration, dormancy